Comparison of renal growth in breast fed and artificial fed infants: a cross-sectional study - Aisha Tariq Alam; Iftikhar Ijaz; Muhammad Umer Mukhtar; Muhammad Ahmad Qureshi; Qasim Mehmood; Farnaz Abbas; Khunsa Junaid (BMC Research Notes, 2023)
Abstract Introduction Renal growth in infancy determines renal function in adulthood and can easily be assessed via infant renal volume. Renal growth is influenced by many endogenous and exogenous factors among which nutrition is of prime importance. Worldwide, infants get their nutrition either from breast milk or formula, both of which have controversial roles in kidney growth and development. Methods A cross-sectional study was done on healthy infants in the Pediatric Nephrology Department of Mayo Hospital, Lahore. These infants were either breastfed or artificially fed and their kidney volumes were noted to determine any significant difference in kidney size. Both informed and written consent was taken before data collection and the data was analyzed using SPSS version 26. Results Out of 80 infants included in our study, 55% were male and 45% were female. The mean age was 8.9 months and the mean weight was 7.6 kg. The mean total kidney volume was 45.38 cm3 and the mean relative kidney volume was 6.12 cm3/kg. No statistical difference in relative renal volume was found between breastfed and artificially fed infants. Conclusion The present study aimed to compare the renal volume and thus renal growth in breastfed versus formula-fed infants. No statistical significance was found in relative renal volume between breastfed and artificially fed infants.